Double teeth in the primary dentition: Case reports from a Nigerian Tertiary Hospital - O. O. Olatosi; E. O. Sote (Nigerian Dental Association, 2011)
The term double tooth is used to describe the developmental dental abnormalities called gemination and fusion. Gemination is an attempted, incomplete division of a single tooth germ during the proliferation stage of odontogenesis, while fusion is the union of two or more independently developing teeth. Although the prevalence of primary double teeth is low, double teeth are of clinical interests because of the associated clinical problems. The clinical problems associated with the condition in the primary dentition are often downplayed for various reasons in spite of their importance. Primary double teeth ought to be carefully investigated so that these clinical problems which may affect the permanent dentition can be effectively managed. Perhaps primary double teeth have not received adequate documentation in our environment because of the low prevalence. This paper presents four primary double teeth in three patients. One of the cases presented occurred bilaterally, a relatively uncommon phenomena. The associated clinical problems are illustrated in the cases and the management discussed. Although primary double teeth are asymptomatic and in some cases may not interfere with function, they do have associated clinical problems. Early diagnosis and regular clinical and radiographic observations are necessary for effective management and appropriate treatment of the anomaly.